2017
DOI: 10.1186/s12917-017-1263-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analyses of the small intestine of pigs in the ex-evacuation zone of the Fukushima Daiichi Nuclear Power Plant

Abstract: BackgroundAfter the accident at the Fukushima Daiichi Nuclear Power Plant, radioactive contaminants were released over a widespread area. Monitoring the biological effects of radiation exposure in animals in the ex-evacuation zone should be continued to understand the health effects of radiation exposure in humans. The present study aimed to clarify the effects of radiation by investigating whether there is any alteration in the morphology and gene expressions of immune molecules in the intestine of pigs and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
(26 reference statements)
1
16
0
Order By: Relevance
“…We have already reported that some of the selected genes did not show any changes; however, some showed significant differences. As previously reported [16], the expression levels of the AIFM1, IFN-γ and TLR3 genes were significantly higher in abandoned pigs than in control pigs. However, the expression levels of cyclin G1, GADD45A, XRCC1, Smad7, XAB2, XPC, OGG1 and EPHX2 were similar in both groups.…”
Section: Real-time Pcr Analysissupporting
confidence: 86%
See 4 more Smart Citations
“…We have already reported that some of the selected genes did not show any changes; however, some showed significant differences. As previously reported [16], the expression levels of the AIFM1, IFN-γ and TLR3 genes were significantly higher in abandoned pigs than in control pigs. However, the expression levels of cyclin G1, GADD45A, XRCC1, Smad7, XAB2, XPC, OGG1 and EPHX2 were similar in both groups.…”
Section: Real-time Pcr Analysissupporting
confidence: 86%
“…As we previously reported that there were no remarkable changes including fibrosis in the intestinal tissues of abandoned pigs [16]. Despite the highly elevated IFN-γ gene expression, there were no pathological or morphological changes in both the abandoned and the non-affected control groups (Fig.11.4).…”
Section: Pathological and Morphological Changes In The Small Intestinementioning
confidence: 49%
See 3 more Smart Citations